2019
DOI: 10.1088/1475-7516/2019/10/059
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar timing array constraints on the induced gravitational waves

Abstract: If the black holes detected by LIGO/VIRGO are primordial black holes (PBHs) sourcing from a large primordial curvature perturbation at small scales, the corresponding induced gravitational waves (GWs) would peak at nanohertz that is detectable by the current and future observations of pulsar timing array (PTA). In this paper we show that with the mass function estimated from the merger rate of LIGO O1 and O2 events, the induced GWs from such a curvature perturbation with a Gaussian narrow peak at some small sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 169 publications
1
42
0
Order By: Relevance
“…A study using current PTA and LIGO data on SGWBs can be found in Refs. [136][137][138][139] and an analysis of future GW prospects in Refs. [33,75,[140][141][142][143][144][145][146]; -SGWB anisotropies: In the far future we may not only observe the GW spectrum but also its anisotropies.…”
Section: Induced Gws Historymentioning
confidence: 99%
“…A study using current PTA and LIGO data on SGWBs can be found in Refs. [136][137][138][139] and an analysis of future GW prospects in Refs. [33,75,[140][141][142][143][144][145][146]; -SGWB anisotropies: In the far future we may not only observe the GW spectrum but also its anisotropies.…”
Section: Induced Gws Historymentioning
confidence: 99%
“…Such an enhancement of the curvature perturbations are often considered in the context of the primordial black hole (PBH) [23][24][25] (see also Refs. [7,[26][27][28][29][30][31]). PBHs have recently been studied by many authors mainly because they can be a dark matter (DM) candidate and may explain the binary black hole merger events observed by LIGO/Virgo [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have proposed different ways to probe such scales, including CMB spectral distortions [98], analyses of Silk damping effects [99], exploiting WIMP properties [100,101] (in the last case assuming they are the main component of dark matter), reconstructing quasar light curves [102] or through the detection of gravitational waves generated by large scalar perturbations, see e.g., Refs. [103][104][105][106][107][108][109][110][111] and references therein for constraints coming from ongoing (PTA [112][113][114]) and future (SKA [115,116], LISA [115,117]) experiments.…”
Section: Introductionmentioning
confidence: 99%